An Analysis of Students’ Learning Style in Speaking English At MAS Proyek Univa Medan - Purba, Hotmaida Dwi Fitriani; Lubis, Yani (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to analyze students' learning styles on English speaking ability at MAS Project Univa Medan school. The research method used by the researcher is descriptive qualitative and the assessment instrument uses interviews and observations. The population in this study were students of MAS Project Univa Medan. The research sample was six students. This research instrument consists of 15 interview questions, and each of the 5 questions is to find out the learning styles of students, namely visual, auditory and kinesthetic. The data results show that there are differences in students' learning styles in speaking ability. Based on the interview results, learning style is one of the most important aspects to improve students' English speaking ability in this school. As a teacher, you have to understand the students' learning styles so that the process of teaching and learning activities runs smoothly. And after knowing students' learning styles, teachers can more easily deliver the material.